2014
DOI: 10.1590/s1413-70542014000200007
|View full text |Cite
|
Sign up to set email alerts
|

Water erosion risk prediction in eucalyptus plantations

Abstract: Eucalyptus plantations are normally found in vulnerable ecosystems such as steep slope, soil with low natural fertility and lands that were degraded by agriculture. The objective of this study was to obtain Universal Soil Loss Equation (USLE) factors and use them to estimate water erosion risk in regions with eucalyptus planted. The USLE factors were obtained in field plots under natural rainfall in the Rio Doce Basin, MG, Brazil, and the model applied to assess erosion risk using USLE in a Geographic Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
4
9
0
4
Order By: Relevance
“…This resulted in a median erosion rate of 4.3 Mg/ha/year and maximum of 10.1 Mg/ha/year. These values are much more comparable to the aforementioned tolerances and lower-impact operations such as cable yarding [2,35,83,85]. This illustrates the difference adequate soil cover makes in predicted erosion rates, especially on such extreme slopes.…”
Section: Erosion Ratessupporting
confidence: 56%
See 2 more Smart Citations
“…This resulted in a median erosion rate of 4.3 Mg/ha/year and maximum of 10.1 Mg/ha/year. These values are much more comparable to the aforementioned tolerances and lower-impact operations such as cable yarding [2,35,83,85]. This illustrates the difference adequate soil cover makes in predicted erosion rates, especially on such extreme slopes.…”
Section: Erosion Ratessupporting
confidence: 56%
“…The low slope class had a K value of 0.063 t h MJ −1 mm −1 , the medium slope class had K values from 0.091 to 0.146 t h MJ −1 mm −1 , and the high Slope class contained K values from 0.157 to 0.237 t h MJ −1 mm −1 . The topographic factor (LS) is a function of slope steepness and slope length; thus, the observed LS values were high compared with other studies on more gentle terrain [85]. Our study areas were characterized by steep, long, continuous slopes.…”
Section: Erosion Ratesmentioning
confidence: 56%
See 1 more Smart Citation
“…Lastly, we should highlight the occurrence of erosion in areas under silviculture, especially where the soil is exposed and during the rainy season. These results confirm the findings of Silva et al (2014). Therefore, the planning of forest activities in this watershed should include the implementation of other conservation practices, in addition to those already used, to eliminate exposed areas containing Cambisols, and forestry should be introduced.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, the weight of the factors land use, soil management, and conservation practices in these biomes does not seem enough to reduce the natural risk of erosion in this sub-watershed, especially because of the undulating relief in Cambisols (which are considered young and shallow) with native and cultivated pastures, as reported by Oliveira et al (2014). Furthermore, according to Silva et al (2014), the estimated risk of water erosion indicated that areas with higher LS and Cambisols should receive more attention. (Source: *Carvalho, 2008) Although the area of the Samambaia River subwatershed is four times larger than the Arrasta-Burro tributary sub-watershed, mean A values were similar in these two areas (39 ± 97 t ha -1 year -1 and 38 ± 87 t ha -1 year -1 , respectively), indicating that land use and occupation was similar in these sub-watersheds.…”
Section: Resultsmentioning
confidence: 98%